Pengaruh Bahan Tambahan Limbah Botol Kaca Pada Kuat Tekan Paving Block: The Effect Of Additional Materials From Glass Bottle Waste On The Compressive Strength Of Paving Block - Indriani, Lilis (​Institute for Researches and Community Services Universitas Muhammadiyah Palangkaraya, 2025)
So far, there have been many industrial waste materials such as onyx sand, iron lathe fibers that have not been utilized optimally. One ofthe industrial waste that has not been used optimally is glass waste This study aims to determine the effect of the addition of glass powder on the compressive strength of paving blocks and polynomial regression relationships between variations in glass powder and compressive strength of paving blocks. The method used in this study was to conduct research in the Laboratory of the Faculty of Engineering, University of Muhammadiyah Palangkaraya with variations in the addition of glass powder 0%, 2%, 4% and 6%. Overall the compressive strength of paving blocks fluctuates with the addition of glass powder instead of partial volume. Concrete compressive strength with a variation of 0% is 33.14 kg / cm2, variation of 2% is 22.65 kg / cm2, variation of 4% is 22.92 kg / cm2 and variation of 6% is 26.38 kg / cm2. Where the compressive strength of paving increases with the addition of glass powder by 6% with an increase ratio of 0.79 from the condition of 0%. This shows that the addition of glass powder at a variation of 6% only reduces the compressive strength of 21% from a variation of 0%. Polynomial regression equation relationship between the addition of glass powder with compressive strength of paving blocks is Y =32.760953 - 623.05279. X + 8717,332985 X 2